Recreational Fishing Effort, Catch, and Harvest for Murray Cod and Golden Perch in the Murrumbidgee River, Australia. (1st July 2015) - Forbes, Jamin P.; Watts, Robyn J.; Robinson, Wayne A.; Baumgartner, Lee J.; Steffe, Aldo S.; Murphy, Jeff J.
Abstract: Recreational fishery management aims to prevent species decline and provide sustainable fisheries. Overfishing has been frequently suggested as a cause of historic fishery declines within the Murray–Darling Basin (MDB), Australia, but there have been few quantitative surveys for providing fishery‐dependent data to gauge status. The Murray Cod Maccullochella peelii and the Golden Perch Macquaria ambigua are important species targeted by recreational fishers across the MDB. The fisheries are controlled by size and bag limits and gear restrictions (both species) as well as a closed season (Murray Cod only). A complemented fisher survey design was used to assess the recreational fishery for both species in a 76‐km reach of the Murrumbidgee River in 2012–2013. Progressive counts were used to quantify boat‐ and shore‐based fishing effort. Catch and harvest rate information was obtained from shore‐based fishers via roving surveys and from boat‐based fishers via bus route surveys. Murray Cod catch rates (fish/angler‐hour) were 0.228 ± 0.047 (mean ± SE; boat based) and 0.092 ± 0.023 (shore based), and harvest rates (fish/angler‐hour) were 0.013 ± 0.006 (boat based) and 0.003 ± 0.001 (shore based). Golden Perch catch rates were 0.018 ± 0.009 (shore based) and 0.002 ± 0.001 (boat based), and harvest rates were 0.006 ± 0.002 (shore based) and 0.001 ± <0.001 (boat based). The Murray Cod fishery had maximal catch and harvest during the 5‐month period after the closed season ended. The closed season aims to protect spawning Murray Cod, but this strategy's effectiveness may have been influenced by high fishing effort and deliberate bycatch during the closure period. To sustain and improve these MDB fisheries, we suggest quantification of catch‐and‐release impacts on spawning Murray Cod, provision of fish passage, re‐stocking of Golden Perch, and education on fishing techniques that minimize Murray Cod bycatch during the closed season. Received October 22, 2014; accepted March 6, 2015